PENGARUH APLIKASI INSEKTISIDA BERBAHAN AKTIF ASETAMIPRID TERHADAP ULAT PENGGULUNG PUCUK (Cydia leucostoma) PADA TANAMAN TEH - Fani Fauziah; Hilman Maulana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Tea Shoot roller (Cydia leucostoma Meyrick) is one potential pests that attack tea shoot, mainly on the new tea shoot after prunning, it caused plant growth becomes stunted. One of control that can be done is by application of insecticides. To determine the effectiveness of insecticide Acetamiprid, the trial has been conducted at Block A7, Gambung field trial, Kabupaten Bandung, during ± 3 months, from October up to December 2016. The trial was designed in Randomized Complete Block Design (RCBD) with five treatments and four replications. The treatment tested covered insecticide Asetamiprid 30% at 1; 0.75; 0.50; 0.25 l/ha and control. The insecticide was sprayed six times using knapsack sprayer one day after plucking, with one week interval. Tea shoot roller attack intensity was observed weekly at the time of plucking. Shoot production, phytotoxicity, as well as rainfall were also observed as a supporting data. The results showed that after three times of spraying, insecticide Asetamiprid 30% at all formulation doses tested could effectively suppress the attack intensity of tea shoot roller. The last observation result, after six times spraying, revealed that the average efficacy level relatively high, i.e. 73,24%. Therefore, for controlling tea shoot roller on tea it could be recommended the use of insecticide Asetamiprid 30%.